The Evaluation of Taking Iron Supplements in Children Aged 6 Months-2 Years - Tuba Hilkay Karapınar; Olgay Bildik; Sultan Aydın Köker; Ersin Töret; Yeşim Oymak; Yılmaz Ay; Bengü Demirağ; Canan Vergin (Galenos Yayinevi, 2017)
Aim: In spite of special supplemental programs for infants, iron deficiency anemia remains relatively common, depending on ethnicity and socioeconomic status. In Turkey, free iron supplement (IS) to infants started in 2004. The aim of this current study is to evaluate the IS in infants. Materials and Methods: Between October 2014 and June 2015, a survey to evaluate the prophylactic use of iron in infants was applied at the polyclinics to the mothers of children aged 6-24 months. Results: Two hundred children were included in the study. IS was not given to 16% of the children. There was no difference in the time of attendance of IS between the premature and mature infants. Only 29% of the children had been given IS for longer than 6 months. While 36% of the children stopped receiving IS due to negligence, 8.5% of them stopped getting it it because of the adverse effect of the drug, and 39.5% of them were informed that IS had been stopped by the doctors. Advisable supplement dosage was used in 40% of the children. Conclusion: A low ratio of reasonable attendance time and dosage for prophylaxis was found. A total of 58 children had used IS for longer than 6 months and for 48 of them (82.7%) IS had been stopped by the doctor. It was thought that regularly examining a healthy child in infancy augmented the attendance time of IS.